Stable isotope ratios in bentho-demersal biota along a depth gradient in the Bay of Biscay: A multitrophic study. (20th September 2016) - Schaal, Gauthier; Nerot, Caroline; Grall, Jacques; Chouvelon, Tiphaine; Lorrain, Anne; Mortillaro, Jean-Michel; Savoye, Nicolas; Brind'Amour, Anik; Paulet, Yves-Marie; Le Bris, Hervé
Abstract: Although stable isotope ratios are increasingly used to investigate the trophic ecology of marine organisms, their spatial variations are still poorly understood in the coastal environment. In this study, we measured the stable isotope composition (δ 13 C, δ 15 N) of suspended particulate organic matter (SPOM) (primary producer), a suspension feeder, the great scallop Pecten maximus (primary consumer), megabenthic decapods and benthic fishes (secondary consumers) along a depth gradient (from 5 m to 155 m depth) across the continental shelf of the Bay of Biscay. Although the three trophic levels exhibited similar δ 13 C patterns along the gradient, the δ 15 N patterns varied between SPOM, scallops and carnivores. The δ 15 N difference between SPOM and scallops decreased with increasing depth, suggesting that non trophic factors may affect the stable isotope composition of scallops at deepest sampling stations. An opposed trend was found between scallops and carnivores, suggesting that the trophic level of these carnivores increased at higher depth, possibly as an adaptation to lower prey abundances. Although our results suggest that primary consumers are suitable to establish isotopic baselines in coastal environments, we stress the need for further studies aiming at characterizing the variability of stable isotopes in coastal biota, and the respective effects of baseline, trophic and metabolic factors in their isotopic composition.